[Ru(bpy)2(NO)SO3](PF6), a Nitric Oxide Donating Ruthenium Complex, Reduces Gout Arthritis in Mice - Rossaneis, Ana C.; Longhi-Balbinot, Daniela T.; Bertozzi, Mariana M.; Fattori, Victor; Segato-Vendrameto, Carina Z.; Badaro-Garcia, Stephanie; Zaninelli, Tiago H.; Staurengo-Ferrari, Larissa; Borghi, Sergio M.; Carvalho, Thacyana T.; Bussmann, Allan J. C.; Gouveia, Florêncio S.; et al. (Frontiers in Pharmacology, 2019)
Monosodium urate crystals (MSU) deposition induces articular inflammation known as gout. This disease is characterized by intense articular inflammation and pain by mechanisms involving the activation of the transcription factor NFB and inflammasome resulting in the production of cytokines and oxidative stress. Despite evidence that MSU induces iNOS expression, there is no evidence on the effect of NO donors in gout. Thus, the present study evaluated the effect of the ruthenium complex donor of NO {[Ru(bpy)2(NO)SO3](PF6)} (complex I) in gout arthritis. Complex I inhibited in a dose-dependent manner MSU-induced hypersensitivity to mechanical stimulation, edema and leukocyte recruitment. These effects were corroborated by a decrease of histological inflammation score and recruitment of Lysm-eGFP+ cells. Mechanistically, complex I inhibited MSU-induced mechanical hypersensitivity and joint edema by triggering the cGMP/PKG/ ATP-sensitive K (+) channels signaling pathway. Complex I inhibited MSU-induced oxidative stress and pro-inflammatory cytokine production in the knee joint. These data were supported by the observation that complex I inhibited MSU-induced NFB activation, and IL-1 expression and production. Complex I also inhibited MSU-induced activation of pro-IL-1 processing. Concluding, the present data, to our knowledge, is the first evidence that a NO donating ruthenium complex inhibits MSU-induced articular inflammation and pain. Further, complex I targets the main physiopathological mechanisms of gout arthritis. Therefore, it is envisaged that complex I and other NO donors have therapeutic potential that deserves further investigation.